MODEL BANK TANAH DALAM KONTEKS GLOBAL: STUDI TENTANG PERAN, TANTANGAN, DAN IMPLIKASINYA TERHADAP PEMBANGUNAN BERKELANJUTAN - Barokah, Umi; Djati, Theresia Silvana Samba (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
Land is a crucial resource that is highly vulnerable to price speculation and monopoly. The fact that land supply is fixed, while the demand for physical development continues to increase alongside population growth, creates complex land-related issues. In some areas, land that should be productive remains idle. This condition has driven the establishment of land banking. The practice of land banking has been implemented in various countries around the world. This study provides an overview of land banking practices in United States, France, Netherlands, and Indonesia through a literature review. The analysis method used in this review is content analysis. The results indicate that land banking aims to ensure land supply for sustainable development in the future, particularly to fulfill human rights and other public interests. However, the effectiveness of land banking may vary depending on several factors, such as local governance, funding mechanisms, community involvement, and the specific objectives for which land banks are established in each country.